A description of 'moral competence' in nursing according to patients' and nurses' perspectives results from an Italian qualitative study - Chiappinotto, Stefania; Dentice, Sara; Gastmans, Chris; Igoumenidis, Michael; Mc Cabe, Catherine; Papastavrou, Evridiki; Suhonen, Riitta; Galazzi, Alessandro; Palese, Alvisa (Universidad de Chile, 2026)
There is a growing need for morally competent nurses to deal with increasingly complex situations and choices as encountered in professional daily life. However, there is no updated evidence about which characteristics, knowledge, skills, and attitudes a morally competent nurse should have and how to support their development. In the context of the EU-Erasmus+ funded project PROMOCON, this study aimed to describe the moral competences of nurses in Italy. A descriptive qualitative study was conducted, involving a purposeful sample of ten nurses and six patients’ representatives in three focus groups. Findings were analyzed in an integrated manner using the content analysis. Nurses are morally competent when they provide personalised care, motivate the patients cared for, protect them in their choices, and set an example with their behaviour. They possess basic ethical, psychological, philosophical, humanistic and legal knowledge; they can understand and relate to others, not only patients/family members but also colleagues or students in difficulty by activating resources when necessary and being empathetic, patient, respectful, responsible, and flexible.